2014
DOI: 10.1063/1.4881278
|View full text |Cite
|
Sign up to set email alerts
|

Robust superconductivity with large upper critical field in Nb2PdS5

Abstract: We report synthesis, structural details, and complete superconducting characterization of very recently discovered [Q. Zhang, Sci. Rep. 3, 1446(2013] Nb 2 PdS 5 new superconductor. The synthesized compound is crystallized in monoclinic structure with C2/m (#12) space group. Bulk superconductivity is seen in both ac/dc magnetic susceptibility and electrical resistivity measurements with superconducting transition temperature (T c ) at 6 K. The upper critical field (H c2 ) being estimated from high field magneto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 34 publications
0
40
0
Order By: Relevance
“…This value exceeds the Pauli paramagnetic limit Hc 2 (0) = 1.84T c by over 3 times [1][2][3][4]. The anisotropic upper critical field ( ~ 3) along with temperature dependent anisotropy was indicative of possible multiband superconductivity [1,5].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…This value exceeds the Pauli paramagnetic limit Hc 2 (0) = 1.84T c by over 3 times [1][2][3][4]. The anisotropic upper critical field ( ~ 3) along with temperature dependent anisotropy was indicative of possible multiband superconductivity [1,5].…”
Section: Introductionmentioning
confidence: 91%
“…Polycrystalline sample of Nb 2 PdS 5 were prepared by solid state reaction method as described elsewhere [4]. Resistivity measurement was done using four probe method in a Cryogenic low temperature and high magnetic field system in conjunction with variable temperature insert.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of high-temperature superconductivity in low-dimensional systems especially in Curates and Iron-based compounds is well celebrated and most haunted phenomenon in condensed matter physics in recent times [1,2]. Recent observation of superconductivity in a strong spin-orbit coupled 4d and 5d transition metal based compound like (Ta/Nb) x Pd(Te/Se/S) y has been arousing high hopes for researchers due to their high critical field [3][4][5][6][7][8][9]. For a compound Ta 2 Pd x S 5 (x<1), Zhang et al first reported type II superconductivity with T c up to 6K [3].…”
Section: Introductionmentioning
confidence: 99%
“…1 National Physical Laboratory, New Delhi-110012, India 2 Sri Murli Manohar Town Post Graduate College Ballia.…”
mentioning
confidence: 99%